2013
DOI: 10.1136/bmjopen-2012-001722
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department visits for fall-related fractures among older adults in the USA: a retrospective cross-sectional analysis of the National Electronic Injury Surveillance System All Injury Program, 2001–2008

Abstract: ObjectivesTo describe the demographic characteristics and incidence of unintentional fall-related fractures among older adults treated in the US hospital emergency departments (EDs).DesignRetrospective observational study.SettingsHospitals’ ED participants in the National Electronic Injury Surveillance System All Injury Program (NEISS-AIP).ParticipantsThe NEISS-AIP was used to generate national estimates of hospital ED visits for unintentional fall-related fracture among adults aged 65 years or older between 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 26 publications
2
27
2
Order By: Relevance
“…Of note, the marked increase in fall-related injury hospitalisation rates nationwide among older adults is consistent with results from a recent study that demonstrated an increase by 50% in the number of hospitalisations for fall-related injuries among persons aged 65 years or older in the USA between 2001 and 2008 3. Moreover, the proportion of hospitalisations for fall-related fractures among older adults increased in the USA from 43% in 2001 to 48% in 2008 6. Upward trends in the number of hospitalisations for fall-related injuries among older adults also have been previously reported in the Netherlands and Finland 2 15.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Of note, the marked increase in fall-related injury hospitalisation rates nationwide among older adults is consistent with results from a recent study that demonstrated an increase by 50% in the number of hospitalisations for fall-related injuries among persons aged 65 years or older in the USA between 2001 and 2008 3. Moreover, the proportion of hospitalisations for fall-related fractures among older adults increased in the USA from 43% in 2001 to 48% in 2008 6. Upward trends in the number of hospitalisations for fall-related injuries among older adults also have been previously reported in the Netherlands and Finland 2 15.…”
Section: Discussionsupporting
confidence: 89%
“…The increase in fall-related injury rates with advancing age and among women has been previously demonstrated by other investigators 5. Gender differences in fall-related fractures treated in ED have been attributed to higher proportions of upper extremity and lower trunk fractures (lumbar spine, pelvis and hip) among women 6. Moreover, this gender disparity in fall-related injuries may be associated with higher prevalence of osteopenia and osteoporosis and lower muscle strength among women 13 14…”
Section: Discussionmentioning
confidence: 69%
“…Fractures are a common consequence of falls, including distal radial fractures (DRFs). Fall-related DRFs occur in the US at a rate of 237/100,000 women aged 65 years or more and 58/100,000 for men and represent nearly 70% of all DRFs to this age group (Chung et al, 2011, Orces, 2013). Osteoporosis is a widely recognized risk factor for DRFs, increasing the risk of fracture nearly nine times for women over 60 (Harness et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The number of older adults, 65 years old or older, treated for a fracture in the ED has increased 24% from 2001 to 2008 and continues to rise with the aging population. 1 In contrast to patients with hip fractures who are treated almost exclusively as inpatients, the majority (50-70%) of older adults with other fractures are treated as outpatients. 1,2 These patients have increased needs for home health care, subacute rehabilitation, and physical and occupational therapy.…”
Section: Introductionmentioning
confidence: 99%
“…1 In contrast to patients with hip fractures who are treated almost exclusively as inpatients, the majority (50-70%) of older adults with other fractures are treated as outpatients. 1,2 These patients have increased needs for home health care, subacute rehabilitation, and physical and occupational therapy. 3 A prospective study of 230 older adults with blunt trauma injuries such as fractures, contusions, and sprains found that 40% had functional decline within the first week of discharge from the ED, and 49% required new social services.…”
Section: Introductionmentioning
confidence: 99%